DEVELOPMENT OF A REAL-TIME POLYMERASE CHAIN REACTION PROTOCOL FOR DIAGNOSIS OF PASTEURELLOSIS - Amirgazin, A.O.; Kairzhanova, A.D.; Shustov , A.V.; Shevtsov , A.B. (Eurasian Journal of Applied Biotechnology, 2019)
Pasteurellosis is a zoonotic disease of vertebrate animals, for which the etiological agent is Pasteurella multocida. The continuous high prevalence of P. multocida and regular periodic outbreaks of pasteurellosis in both wild and domestic animals, especially in the wild saiga populations in Kazakhstan, underscores the importance of developing a local molecular diagnostic system. Accordingly, the goal of the present study was to develop a real-time polymerase chain reaction (PCR) protocol to identify all serovars of P. multocida. The envC, ruvB, and QseC genes were chosen as targets, and real-time PCR protocols were developed using three pairs of primers and corresponding fluorescent probes characterized by high efficiency, sensitivity, and specificity. The sensitivity of the developed protocols to the sequences of the envC and QseC genes was 2.38 fg, and that to the ruvB gene was 76 pg. The high specificity of the PCR protocol was confirmed with a collection of samples from 92 species of bacteria and three species of higher eukaryotic organisms. The commercialization of these developed protocols will allow for the production of highly effective PCR test systems, and improve the diagnosis and treatment of pasteurellosis.